2011
DOI: 10.1007/s11423-011-9217-2
|View full text |Cite
|
Sign up to set email alerts
|

Online discussion compensates for suboptimal timing of supportive information presentation in a digitally supported learning environment

Abstract: This study used a sequential set-up to investigate the consecutive effects of timing of supportive information presentation (information before vs. information during the learning task clusters) in interactive digital learning materials (IDLMs) and type of collaboration (personal discussion vs. online discussion) in computer-supported collaborative learning (CSCL) on student knowledge construction. Students (N = 87) were first randomly assigned to the two information presentation conditions to work individuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Despite the advantages of online collaboration, Noroozi et al () concluded that face‐to‐face interaction still provides students with more opportunities for nonverbal communication, social interaction, turn taking, opportunities for feedback, and group understanding, especially if students are more sociable (Trinder, ). However, as students are spending increasing amounts of time on mobile devices, they may develop strategies such as the use of emoticons or other paralinguistic devices to mitigate the absence of these nonverbal cues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the advantages of online collaboration, Noroozi et al () concluded that face‐to‐face interaction still provides students with more opportunities for nonverbal communication, social interaction, turn taking, opportunities for feedback, and group understanding, especially if students are more sociable (Trinder, ). However, as students are spending increasing amounts of time on mobile devices, they may develop strategies such as the use of emoticons or other paralinguistic devices to mitigate the absence of these nonverbal cues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital learning modules are increasingly introduced in higher education, including in the field of biotechnology and molecular life sciences [1][2][3]. These modules can serve various purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Argumentation is a vehicle for collaborative learning process not only for traditional forms of classrooms but also for blended and online learning settings such as open and distance learning programmes in higher education (see Noroozi, Busstra, Mulder, Biemans, Tobi, Geelen, et al, 2012). Argumentation is considered to be significant to education due to the importance of discourse in the acquisition of scientific knowledge (Osborne, 2010).…”
Section: Introductionmentioning
confidence: 99%